Interaction between two nonpoint nanoparticles: Implementation to biology and medicine - Lozovski, V.; Lysenko, V.; Piatnytsia, V.; Spivak, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2012)
A new mechanism of interaction between two nanoparticles characterized by
their dimensions and shape has been proposed. The mechanism is based on the local-field
induced dipole momentum interaction with taking into account nonlinear polarizabilities
of the particles. The dipole momentum induced in the particles has a fluctuating nature.
The proposed mechanism of interparticle interaction leads to formation of both repulsive
and attractive parts having the minimum at the distance between the particles close to
their linear dimensions. The profile and strength of the potential depend both on
dimensions and shapes of the particles as well as on their mutual orientation.
Implementation of the discussed interaction conception to biology and medicine has been
discussed.